PENERAPAN ASAS RETROAKTIF DALAM PELANGGARAN HAK ASASI MANUSIA - Ramadani, Fitri; Halimang, St; Risal, Chaerul (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
This research aims to describe the application of the Retroactive Principle in Human Rights Violations. The assertion of human rights in Indonesia experiences a very definite dilemma in law enforcement considering the many past human rights violations that have not been resolved. Thus, this research uses a type of library research with a normative juridical approach and a syar’I approach. This data collection method involves studying several primary data sources extracted from scientific works, documents and relevant books. The research results show that the retroactive principle is a principle or legal principle that can be implemented in upholding human rights, with 4 cumulative conditions, namely: 1) The criminal act committed is a serious human rights violation; 2) the nature of justice must be international; 3) justice is ad-hoc; 4) the government’s inability to prosecute crimes, both in terms of cruelty and damage.